Higher concentrations of matrix metalloproteinases in bronchoalveolar lavage fluid of patients with adult respiratory distress syndrome - Torii, K; Iida, K; Miyazaki, Y; Saga, S; Kondoh, Y; Taniguchi, H; Taki, F; Takagi, K; Matsuyama, M; Suzuki, R (American journal of respiratory and critical care medicine, 1997)
This study was designed to investigate possible involvement of type IV collagenolytic matrix metalloproteinases (MMPs; 72-kDa type IV collagenase [MMP-2], 92-kDa type IV collagenase [MMP-9]), and the respective specific tissue inhibitors of these MMPs (TIMP-2 and TIMP-1) in the development of adult respiratory distress syndrome (ARDS). We determined the concentrations of these enzymes in the bronchoalveolar lavage fluid (BALF) from patients with ARDS using newly developed sensitive one-step sandwich enzyme immunoassay methods. BALF obtained from the 17 patients and eight healthy volunteer control subjects were also used for the analysis of the number of the cellular component. Concentrations of the 7S portion of type IV collagen and laminin in the BALF were measured as markers of basement membrane disruption. In the BALF from the ARDS patients, the concentrations of MMP-2 (66.7 +/- 57.0 ng/ml versus < 7.0 ng/ml for controls, p < 0.01) and MMP-9 (118.0 +/- 309.3 ng/ml versus 9.0 +/- 9.5 ng/ml for controls, p < 0.05), and the specific inhibitor of MMP-9 (TIMP-1) (161.0 +/- 145.0 ng/ml versus < 50 ng/ml for controls, p < 0.01) were significantly higher compared with those for healthy control subjects. In the ARDS patients, the concentrations of MMP-2 correlated both with those of 7S collagen and laminin; MMP-9 with the concentration of 7S collagen and the number of neutrophils. These findings suggest that the increased concentration of collagenolytic MMPs in lung plays a role in the pathogenesis of ARDS.